Pengaruh Ukuran Partikel Serbuk Kalsium Oksida (CaO) Sebagai Adsorben Untuk Meningkatkan Kadar Etanol Teknis: Pengaruh Ukuran Partikel Serbuk Kalsium Oksida (CaO) Sebagai Adsorben Untuk Meningkatkan Kadar Etanol Teknis - Lamuru, Afrianti S; Mahirullah; Juita , Sri (Jurnal Jejaring Matematika dan Sains, 2023)
The research studied method of increasing technical alcohol levels by using Calcium Oxide (CaO) adsorbent in adsorption distillation. Alcohol can be used as an alternative fuel or fuel additive to increase the octane number of the fuel so as to produce low carbon emissions. So, it is very important alcohol purification. One method for purifying alcohol is adsorption distillation. The purpose of this study was to determine the effect of the particle size of CaO adsorbent powder in the adsorption distillation method. The ethanol used as feed is ethanol of 70% and 96%. The results showed the increase in ethanol content with a particle size of 100 mesh, 150 mesh and 200 mesh, the highest final ethanol content was obtained at a particle size of 200 mesh, where at an initial concentration of 70% ethanol after the adsorption process increased to 88.50%, while the ethanol content the lowest was obtained at 100 mesh with a final content of 87%. Likewise, the initial concentration of 96% ethanol after the adsorption process increased to 98.25% at a particle size of 200 mesh, while the lowest concentration was obtained at a particle size of 100 mesh with a final grade of 97.90%. From the results of the study showed that particle size greatly influences the increase in ethanol content. The smaller the particle size used, the greater the adsorption speed. The smaller the particle size, the greater the surface area, so that more water is absorbed and the resulting ethanol concentration is greater.